Johannesburg The Elusive Metropolis - Abdoumaliq, Simone; Achal, Prabhala; Achille, Mbembe; Arjun, Appadurai; Carol A., Breckenridge; David, Bunn; Fred, De Vries; Frederic, Le Marcis; Grace, Khunou; John, Matshikiza; Jonathan, Hyslop; Julia, Hornberger; et al. (a Public Culture Book, 2008)
Johannesburg: The Elusive Metropolis is a pioneering effort to insert South Africa's largest city into urban theory, on its own terms. Johannesburg is Africa's premier metropolis. Yet theories of urbanization have cast it as an emblem of irresolvable crisis, the spatial embodiment of unequal economic relations and segregationist policies, and a city that responds to but does not contribute to modernity on the global scale. Complicating and contesting such characterizations, the contributors to this collection reassess classic theories of metropolitan modernity as they explore the experience of "city-ness" and urban life in post-apartheid South Africa. They portray Johannesburg as a polycentric and international city with a hybrid history that continually permeates the present.